2021
DOI: 10.3390/agronomy11071276
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Soil Tillage Systems and Crop Residues on the Composition of Weed Communities

Abstract: The composition of weed communities in agricultural crops is dependent on soil properties and the applied agronomic practices. The current study determined the effect of different tillage systems and crop residue on the soil weed community composition. The research programme encompassed 2013–2015 in a long-term field experiment located in the Experimental Station of Vytautas Magnus University in Lithuania. The soil type in the experimental field was qualified as Endocalcaric Stagnosol (Aric, Drainic, Ruptic, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
3
3
0
1
Order By: Relevance
“…Species richness in the present study showed an apparent decrease with crop residues retention during the observation period (Figure 3a), i.e., crop residues retention significantly decreased species richness of the weed community, consistent with other studies [2,37]. These findings suggest that long term crop residues retention may reduce the weed species richness in the summer maize field.…”
Section: Effects Of Crop Residues Retention On the Weed Community Diversitysupporting
confidence: 92%
“…Species richness in the present study showed an apparent decrease with crop residues retention during the observation period (Figure 3a), i.e., crop residues retention significantly decreased species richness of the weed community, consistent with other studies [2,37]. These findings suggest that long term crop residues retention may reduce the weed species richness in the summer maize field.…”
Section: Effects Of Crop Residues Retention On the Weed Community Diversitysupporting
confidence: 92%
“…In particular, some authors note that there is no statistical difference in the intensity of weed infestation depending on the treatment, but point to significant changes in the species composition of weeds (Winkler et al, 2023). While others have pointed out that minimising tillage increases weed infestation, leading to a greater reliance on herbicides compared to conventional tillage (Steponavičienė et al, 2021). The latter statement was true in the current research.…”
Section: Soil Cultivation (Factor A)supporting
confidence: 49%
“…In particular, some authors note that there is no statistical difference in the intensity of weed infestation depending on the treatment, but point to significant changes in the species composition of weeds (Winkler et al, 2023). While others have pointed out that minimising tillage increases weed infestation, leading to a greater reliance on herbicides compared to conventional tillage (Steponavičienė et al, 2021). The latter statement was true in the current research.…”
Section: Soil Cultivation (Factor A)supporting
confidence: 49%